Being Indian : the truth about why the twenty-first century will be India's - Varma, Pavan K., 1953- (New Delhi : Penguin Books, 2004)
On the changing perspectives in social life of East Indians and their attitudes; reflecting on the socio-political mileau in India.
Includes bibliographical references (p. [214]-227) and index.
Keywords: East Indians -- Attitudes; India -- Politics and government -- 1977-; India -- Social life and customs -- 21st century